Hsa_circ_0103232 promotes melanoma cells proliferation and invasion via targeting miR-661/RAB3D. Issue 17 (2nd September 2022) - Lin, Xing; Zhong, Liang; Wang, Nian; Chu, Xuan; Liu, Beizhong
ABSTRACT: Little is known about the role of hsa_circ_0103232 in melanoma. This study researched the role of hsa_circ_0103232 in melanoma progression. Hsa_circ_0103232 expression in clinical tissues of melanoma patients and melanoma cells was detected by qRT-PCR. Hsa_circ_0103232 localization in melanoma cells was visualized by fluorescence in situ hybridization. Hsa_circ_0103232 effect on melanoma cells viability, proliferation, migration, and invasion was explored by cell counting kit-8 (CCK-8) assay, Edu experiment, wound healing assay, and Transwell experiment. RNA pull-down assay and dual-luciferase reporter gene assay were performed to verify the binding of hsa_circ_0103232 with miR-661, and the binding of miR-661 and RAB3D. Xenograft tumor models were constructed. Western blot and immunohistochemistry were used for protein expression detection. Hsa_circ_0103232 expression was increased in melanoma patients, indicating lower overall survival. Hsa_circ_0103232 was mainly expressed in the cytoplasm of melanoma cells. Silencing hsa_circ_0103232 suppressed melanoma cell viability, proliferation, migration, invasion, and epithelial–mesenchymal transition (EMT) ( P < 0.01). Hsa_circ_0103232 functioned as a sponge of miR-661 to increase RAB3D expression. miR-661 overexpression partially reversed hsa_circ_0103232 promoting effect on melanoma cells viability, proliferation, migration, invasion, and EMT ( P < 0.01). In melanoma patients, hsa_circ_0103232 expression was negatively correlated with miR-661 and positively correlated with RAB3D. Silencing hsa_circ_0103232 suppressed melanoma cell growth in vivo and Ki67 and RAB3D expression in xenograft tumors ( P < 0.01). Hsa_circ_0103232 is a tumor promoter in melanoma to enhance malignant phenotype and growth in vivo via sponging miR-661/RAB3D. Hsa_circ_0103232 may be a novel target for melanoma treatment.